Allocation of Tabarru's Funds in Endowment Premium - Fitriyati, Nina; Zharifah, Zharifah; Zulkifli, Dhea Urfina (UIN Sumatera Utara, 2023)
In general, the premiums paid by participants in Islamic insurance are allocated into three components with specific proportions: administrative costs, participants' savings, and Tabarru's funds (mutual aid funds). Participants' savings and Tabarru's funds are invested according to Sharia principles, and the returns are shared (Mudharabah) between the participants and the company. This study analyses the allocation of Tabarru's funds and participant savings about the size of premiums using the Endowment method. Additionally, the investment results from Tabarru's funds and participant savings, as well as their distribution to participants and the insurance company, will be simulated. Premium calculations utilize the Indonesian Mortality Table (TMI) for the year 2011. The simulation results indicate that administrative costs and investment returns from premiums managed for male participants are larger than those for female participants. Therefore, the claim amount for male participants is likely to be higher compared to the claim, amount for female participants.